Surface-enhanced Raman spectroscopy study of 4-ATP on gold nanoparticles for basal cell carcinoma fingerprint detection - Quynh, Luu Manh; Nam, Nguyen Hoang; Kong, K.; Nhung, Nguyen Thi; Notingher, Ioan; Henini, M.; Luong, Nguyen Hoang (Springer, 2016)
The surface-enhanced Raman signals of 4-aminothiophenol (4-ATP) attached to the surface of colloidal gold nanoparticles with size distribution of 2 to 5 nm were used as a labeling agent to detect basal cell carcinoma (BCC) of the skin. The enhanced Raman band at 1075 cm-1 corresponding to the C-S stretching vibration in 4-ATP was observed during attachment to the surface of the gold nanoparticles. The frequency and intensity of this band did not change when the colloids were conjugated with BerEP4 antibody, which speciﬁcally binds to BCC. We show the feasibility of imaging BCC by surface-enhanced Raman spectroscopy, scanning the 1075 cm-1 band to detect the distribution of 4ATP-coated gold nanoparticles attached to skin tissue ex vivo.